Transgender youth: current concepts - Stephen M. Rosenthal (Korean Society of Pediatric Endocrinology, 2016)
In many countries throughout the world, increasing numbers of gender nonconforming/transgender youth are seeking medical services to enable the development of physical characteristics consistent with their experienced gender. Such medical services include use of agents to block endogenous puberty at Tanner stage II with subsequent use of cross-sex hormones, and are based on longitudinal studies demonstrating that those individuals who were first identified as gender dysphoric in early or middle childhood and continue to meet the mental health criteria for being transgender at early puberty are likely to be transgender as adults. This review addresses terms and definitions applicable to gender nonconforming youth, studies that shed light on the biologic determinants of gender identity, current clinical practice guidelines for transgender youth, challenges to optimal care, and priorities for research.